Industrial noise level study in a wheat processing factory in Ilorin, Nigeria - Ibrahim, I; Ajao, K.R.; Aremu, S.A. (Zielona Góra: Uniwersytet Zielonogórski)
An industrial process such as wheat processing generates significant noise which can cause adverse effects on workers and the general public. This study assessed the noise level at a wheat processing mill in Ilorin, Nigeria. A portable digital sound level meter HD600 manufactured by Extech Inc., USA was used to determine the noise level around various machines, sections and offices in the factory at pre-determined distances.
Keywords: wheat processing; noise level; digital sound meter; questionnaire; hearing protector